New data on the acanthocephalan Neoechinorhynchus villoldoi Vizcaíno, 1992 (Neoechinorhynchidae: Acanthocephala), based on specimens found in Austrolebias bellottii (Steindachner, 1881) (Rivulidae: Cyprinodontiformes) from Punta Indio, Argentina - Montes, Martin Miguel (2017)
In a survey of parasites on the killifish, Austrolebias bellottii from Punta Indio and Magdalena, Argentina, the acanthocephalan Neoechinorhynchus villoldoi was found. This parasite had not been recorded since 1992 when it was described for the first time parasitizing Corydoras paleatus (Jenyns, 1842). The type material of N. villoldoi was examined, and with addition of the new specimens, the measurements range was extended. This is the first record of an acanthocephalan in the annual fish, A. bellottii